2016
DOI: 10.1007/s40090-016-0103-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical approach of Kalmegh leaf extract on the corrosion behavior of aluminium alloy in alkaline solution

Abstract: Introduction The effect of Kalmegh leaf extract (KLE) on the corrosion behavior of aluminium in 1 M NaOH solution was studied using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) studies.Results Inhibition efficiency (g%) increased with increasing the concentration of extract and maximum inhibition efficiency observed is 82.24 and 82.45% from EIS and PDP studies, respectively, at higher concentration. Conclusion The adsorption of the inhibitor on aluminium surface was in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The drift in OCP value depends on the presence and absence of oxygen and nature of corroding material. It was noticed from results OCP values increases in a positive direction as SiC content increases in different inorganic acid medium and 3.5% neutral chloride medium [35]. But in hybrid composites there is a slight decrease in OCP value in inorganic HCl and neutral NaCl mediums, maybe due to the presence of graphite, galvanic coupling takes place in hybrid composites.…”
Section: Electrochemical Measurements Ocp Measurementsmentioning
confidence: 85%
“…The drift in OCP value depends on the presence and absence of oxygen and nature of corroding material. It was noticed from results OCP values increases in a positive direction as SiC content increases in different inorganic acid medium and 3.5% neutral chloride medium [35]. But in hybrid composites there is a slight decrease in OCP value in inorganic HCl and neutral NaCl mediums, maybe due to the presence of graphite, galvanic coupling takes place in hybrid composites.…”
Section: Electrochemical Measurements Ocp Measurementsmentioning
confidence: 85%
“…The increased value of corrosion efficiency is because of the coating layer manages to protect the substrate both physically and chemically from the attack of corrosive species unto the substrates. Previous studies showed that Kalmegh extract affects both the anodic sites and cathodic sites, which is a representation of its mixed-type inhibition characteristic where this can be identify by a significant change in the value of corrosion current density (i corr ) and the Tafel constant as the extract was added into the coating [20]. Table 4 shows the value of corrosion rate (CR) where the result displayed that i corr decreased with the addition of Kalmegh extract.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 93%
“…A study performed using Kalmegh leaves extract (KLE) as an inhibitor in the NaOH solution showed that the extract increased the inhibition efficiency up to 82.24% and 82.45% for both analysis of EIS and PP. Moreover, KLE was also found out to be a mixed type inhibition with a dominant cathodic effect [20]. As a component in a coating, a research suggested that the incorporation of KLE as an additive yields a significant increase in coating performance when it is used up to 6 wt.%, and further addition caused a significant drop in the barrier quality [21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its useful properties and abundance, aluminium finds wide applications in various industries such as automotive, aerospace, construction and electrical power generation. [1] In specific, one notable application of aluminium is in aluminium-air batteries due to its high energy density (8.1 kW h kg -1 ) and electrode potential of 2.35 V (vs. standard hydrogen electrode) in an alkaline medium. [2,3] Among various types of corrosion observed in aluminium, pitting corrosion is observed under stagnant conditions of the corrosion medium.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, different researchers have studied the aptitude of different plants as corrosion inhibitors for aluminium corrosion in alkaline medium. For example, Chaubey et al [1] have studied the inhibitive properties of Kalmegh leaf extract on aluminium alloy corrosion in 1 M NaOH and found a maximum inhibition efficiency of 82%. In another study, Geetha et al [12] used Solanum trilobatum leaves extract as a corrosion inhibitor for aluminium in 1 M NaOH and found a maximum inhibition efficiency of 93%.…”
Section: Introductionmentioning
confidence: 99%